ANALYSIS OF “JOGJA ISTIMEWA” PROGRAM BASED ON THE PARTICIPANTS’ EVALUATION - Partha, Jati Kanya; Axelandra, Aaron Desvara; Astuti, R.A. Vita (LATTE: A Journal of Language, Culture, and Technology ISSN 3063-0754, 2024)
This research paper examines "Jogja Istimewa" (Jogist) program, a mandatory cultural immersion experience for students at Universitas Atma Jaya Yogyakarta. The program, organized by the Language and Culture Training Office (KPBB), aims to introduce students, many of whom are from outside Yogyakarta, to the region’s unique cultural practices and etiquette. The program, initially classroom-based, now involves hands-on activities at Kraton Ngayogyakarta Hadiningrat and other cultural sites. Students participate in hands-on activities such as dance, music, fashion, and archery, guided by experts from the Kraton. The study uses interviews, observations, and document analysis to assess the program's effectiveness in teaching Yogyakarta's culture and etiquette to students, who mostly come from outside the region. The program’s success is attributed to its interactive approach, the expertise of the resource persons, and the commitment of UAJY and KPBB to preserving and promoting Yogyakarta's cultural heritage. Findings suggest the on-site program is significantly more impactful than the previous classroom model, receiving positive feedback from students and instructors. “Jogist Program” has values in fostering cultural understanding and encouraging students to apply these lessons in their daily lives. The paper offers several recommendations for improving future program iterations.